Negotiating environmental change new perspectives from social science - Berkhout, F. (Frans); Leach, Melissa; Scoones, Ian.; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2003)
This book by leading researchers presents a critical review of debates in environmental social science over the past decade. Three broad areas are covered in ten chapters: the problems of scientific uncertainty and its role in shaping environmental policy and decisions; the development of institutional frameworks for governing natural resources; and the link between economic and technological change and the environment. The book begins with an overview essay examining how perspectives across environmental social science have shifted over the past decade and looking forward to the emergence of new research agendas.
1. Shifting perspectives in environmental social science -- 2. Risk, uncertainty and precaution : some instrumental implications from the social sciences -- 3. Economics and sustainable development : what have we learnt, and what do we still need to learn? -- 4. Deliberative democracy and environmental decision-making -- 5. Governance and the environment -- 6. After Seattle : what next for trade and the environment? -- 7. Governing natural resources : institutional adaptation and resilience -- 8. Sustainable business organizations? -- 9. Inducing, shaping, modulating : perspectives on technology and environmental policy -- 10. (Un) sustainable consumption.
Includes bibliographical references and index.
Keywords: Environmental policy; Environmental policy -- Research -- Great Britain; Electronic books